2021
DOI: 10.3390/children8090760
|View full text |Cite
|
Sign up to set email alerts
|

ABO Incompatible Liver Transplantation in Children: A 20 Year Experience from Centres in the TransplantChild European Reference Network

Abstract: An increasing number of AB0-incompatible (AB0i) liver transplantations (LT) are being undertaken internationally in recent years due to organ shortages and the need for urgent transplantation. The aim of our study was establish the value of ABOi LT from available retrospective results of AB0i pediatric liver transplantations performed in European reference centers now belonging to the TransplantChild, European Reference Network (ERN). Data from medical records were analyzed, including demographic data, diagnos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…In particular, patient mortality after 2011 (19%) was significantly lower ( P < 0.05) than that before 2011 (33%). However, mortality was higher in the TRANSPLANT-CHILD patient cohort 46 than in others. 44,45…”
Section: Specific Patient Populationsmentioning
confidence: 63%
See 2 more Smart Citations
“…In particular, patient mortality after 2011 (19%) was significantly lower ( P < 0.05) than that before 2011 (33%). However, mortality was higher in the TRANSPLANT-CHILD patient cohort 46 than in others. 44,45…”
Section: Specific Patient Populationsmentioning
confidence: 63%
“…In particular, patient mortality after 2011 (19%) was significantly lower (P < 0.05) than that before 2011 (33%). However, mortality was higher in the TRANSPLANT-CHILD patient cohort 46 than in others. 44,45 New Complications Associated With ABO-I LDLT AMR and infections are the most common complications of ABO-I LDLT.…”
Section: Pediatric Abo-i Ldltmentioning
confidence: 63%
See 1 more Smart Citation
“…A recent multicenter European collaborative report described the outcomes after ABOi and presented the various perioperative medical management strategies for ABOi LT ( 8 ). There was a high variability in practice, with no one strategy superior to the others.…”
Section: Discussionmentioning
confidence: 99%
“…Patient and graft survival were also noted to be lower than with ABO identical or compatible (ABOc) grafts ( 5 , 6 ). However, recently published studies showed improved outcomes after ABOi ( 7 , 8 ). The age of the recipient was shown to be an important predictive factor of outcomes, where age greater than 1 year at the time of ABOi LT was associated with an increased morbidity and mortality ( 9 , 10 ).…”
Section: Introductionmentioning
confidence: 99%